Sonographic evaluation of pleural fluid in a large group of adult healthy individuals : end trial results - Vidmar Kocijančič, Ksenija (Array, 2009)
Abstract: This partly prospective, partly retrospective trial was performed in adult healthy volunteers to confirm the prevalence of sonographically visible physiological pleural and to establish possible individual variations of the presence and amount of pleural fluid over time as well as to asses relations in between pleural fluid and individual characteristics like age, sex, body mass index, smoking history and hormone therapy (in woman). A reliable threshold between normal and pathological pleural fluid findings was determined. Prospective chest sonography of both pleural spaces was performed with 3–12 MHz transducer in 71 randomly selected healthy adults and presence of pleural fluid was evaluated and measured as an anechoic layer at least 2 mm in thickness. Each individual was reexamined three times in two to four months intervals.